Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1159/000373885
|View full text |Cite
|
Sign up to set email alerts
|

Normal Development of Human Brain White Matter from Infancy to Early Adulthood: A Diffusion Tensor Imaging Study

Abstract: Diffusion tensor imaging (DTI), which measures the magnitude of anisotropy of water diffusion in white matter, has recently been used to visualize and quantify parameters of neural tracts connecting brain regions. In order to investigate the developmental changes and sex and hemispheric differences of neural fibers in normal white matter, we used DTI to examine 52 healthy humans ranging in age from 2 months to 25 years. We extracted the following tracts of interest (TOIs) using the region of interest method: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 33 publications
6
63
0
1
Order By: Relevance
“…Studies in the brain have reported age-related changes in the DTI parameters to describe the normal developmental characteristics from infancy to adulthood. 17 In addition, it is proposed that changes in DTI parameters in the brain as a function of age may result from decreasing water content, myelination of fiber tracts, and the thickening diameter of fiber tracts. 18 The SC is an extension of the brain, transmitting messages from the brain to the periphery and vice versa; and similar physiologic processes may occur in the SC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the brain have reported age-related changes in the DTI parameters to describe the normal developmental characteristics from infancy to adulthood. 17 In addition, it is proposed that changes in DTI parameters in the brain as a function of age may result from decreasing water content, myelination of fiber tracts, and the thickening diameter of fiber tracts. 18 The SC is an extension of the brain, transmitting messages from the brain to the periphery and vice versa; and similar physiologic processes may occur in the SC.…”
Section: Discussionmentioning
confidence: 99%
“…[30]), or even extended to studies of development in sub-cortical brain areas (e.g. [31]). However, this procedure is resource intensive.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been far fewer studies on the development of pathways from birth to adult ages. A few studies (Cancelliere et al., 2013; Uda et al., 2015) investigated white matter pathways from infant to adult ages looking at growth curves of pathways, but without specifically studying the cerebellar pathways and without considering laterality.…”
Section: Introductionmentioning
confidence: 99%